Biochemical Diversity and Elemental Composition of Irpex lacteus and Hexagonia nitida: Towards Sustainable Exploitation of Fungal Resources - Akshay B. Gulave; B.M. Sakdeo; M. B. Kanade (The Bioscan, 2024)
To carry out Mycochemical analysis of Irpex lacteus and Hexagonia nitida by conventional and advanced techniques. Extracts of fungal material was prepared using eight different solvents on the basis of their polarity index. Mycochemical analysis was carried out by using different reagents, florescence analysis, percent extractive value, Fourier transform infrared spectroscopy, Atomic absorption spectroscopy and High percent extractive value was recorded for methanolic extract of Irpex lacteus (56 %). Mycochemical analysis, FTIR and UV- visible spectroscopy showed the presence of, flavonoids, terpenes, phenolics alkaloids, anthraquinones, and saponins and their presence has been reported in Irpex lacteus and Hexagonia nitida. Trace elements have shown highest concentration in Irpex lacteus followed by Hexagonia nitida. Obtained results show the potential of this fungal material to be used in herbal drugs.